The Effect of Stroke on Middle Cerebral Artery Blood Flow Velocity Dynamics During Exercise. Issue 4 (October 2019) - Kempf, Katie S.; Whitaker, Alicen A.; Lui, Yumei; Witte, Emily; Perdomo, Sophy J.; Ward, Jaimie L.; Eickmeyer, Sarah; Ledbetter, Luke; Abraham, Michael; Billinger, Sandra A.
Abstract : Background and Purpose: Previous work demonstrates that older adults have a lower response in the middle cerebral artery velocity (MCAv) to an acute bout of moderate-intensity exercise when compared with young adults. However, no information exists regarding MCAv response to exercise after stroke. We tested whether MCAv response to an acute bout of moderate-intensity exercise differed between participants 3 months after stroke and an age- and sex-matched control group of older adults (CON). A secondary objective was to compare MCAv response between the stroke- and non-stroke-affected MCAv. Methods: Using transcranial Doppler ultrasound, we recorded MCAv during a 90-second baseline (BL) followed by a 6-minute moderate-intensity exercise bout using a recumbent stepper. Heart rate (HR), end-tidal CO2 (PET CO2 ), and beat-to-beat mean arterial blood pressure (MAP) were additional variables of interest. The MCAv response measures included BL, peak response amplitude (Amp), time delay (TD), and time constant (τ). Results: The Amp was significantly lower in the stroke-affected MCAv compared with CON ( P < 0.01) and in the nonaffected MCAv compared with CON ( P = 0.03). No between-group differences were found between TD and τ. No significant differences were found during exercise for PET CO2 and MAP while HR was lower in participants with stroke ( P < 0.01). Within the group of participants with stroke, no differences were found between the stroke-affected and non-stroke-affected sides for any measures. Discussion and Conclusions: Resolution of the dynamic response profile has the potential to increase our understanding of the cerebrovascular control mechanisms and test cerebrovascular response to physical therapy–driven interventions such as exercise. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A284 ). Abstract : Supplemental Digital Content is Available in the Text.